Studi Tentang Nilai Viskositas Madu Hutan dari Beberapa Daerah di Sumatera Barat untuk Mengetahui Kualitas Madu - Devina Apriani (Department of Physics – Universitas Negeri Padang UNP, 2013)
Abstract- The research is motivated by the increasing needs of the community will be honey, especially honey forests believed to have the quality to maintain good health. The amount of honey on the market are not guaranteed authenticity. This requires a study of the quality of forest honey produced, particularly in some areas of West Sumatra. Quality honey can be determined by several parameters, one of which is of value owned viscosity of honey. This research is a descriptive study conducted in a laboratory data collection Material Physics and Biophysics Faculty UNP and School Laboratory Chemical Analyst (SMAK) Padang in May to July 2012. The samples were examined in this study is a honey of a few areas in West Sumatra include Agam District, Tanah Datar regency Sijunjung, Solok and Padang Panjang City as independent variables and the dependent variable viscosity grades. Each sample was measured viscosity values ​​using Ostwald viscometer. The results of measurements of viscosity grades of honey obtained as follows: honey from 8.3754 Poise Agam District, Tanah Datar at 17.5646 Poise, Poise District Sijunjung at 10.9615, 17.9445 Solok for Poise, and City fields lengths at 3.4588 Poise. Viscosity grades of honey derived from Solok, Tanah Datar regency Sijunjung and has a value greater than the Indonesian National Standards (SNI), which according to the ISO viscosity grades of honey are at least 10 Poise. Keywords: Honey, Viscosity, and Quality Honey